Dalla miseria alla diseguaglianza. Le inchieste sulla povertà in Italia, 1951-1985 - La Rovere, Luca (Disuguaglianza e generazioni in Italia 1914-2008, 2026)
The aim of this contribution is to show how slowly public institutions have moved from an impressionistic and merely descriptive view of poverty to an attempt of defining it in terms of inequality, as a structural and long-term feature of Italian society. Three moments are examined in which political parties, scholars, and public opinion attempted to bring the issue of poverty to light and confront it: the Parliamentary Inquiry on Poverty and Means to Combat It in 1951; the Report on Poverty in Italy, developed within the framework of a European initiative in 1979; and the Gorrieri Commission on Poverty, established by the Craxi government in 1985. The three investigations had different outcomes, both in terms of the investigative tools used and the actual implementation of measures to counter the phenomenon.